Effectiveness, Safety and Tolerability of Combination of Amlodipine and Valsartan in Hypertensive Patients (Cardiovascular Journal, 2016)
Background: Hypertension is a major public health challenge worldwide and majority of patients fail to achieve blood pressure control with monotherapy. The purpose of the present study was to assess effectiveness of single pill combination of amlodipine and valsartan as anti-hypertensive therapy under real life conditions.Methods: This prospective, non-interventional, open-label, non-comparative observational, multicenter study was conducted from July 2013 to October 2014. This study was carried out among the hypertensive patients who were treated with single pill of amlodinpine and valsartan. Data were collected at baseline and end of study time points.The study was considered as completed for an individual patient when the treatment was completed approximately 26 ± 8 weeks.The assignment of the patient to the therapy was decided within the current practice and the medical indication, and was clearly separated from the decision to include the patient in the study.Results: The study enrolled 278 patients. Of these 236(84.9%) patients completed the study. Nonserious adverse events were reported in 19(6.8%) cases. During enrollment of the study majority patients were in the more than 140 mmHg systolic BP group which was 205(73.7%) patients which was gradually decreased to 101(36.3%) and 59(21.2%) at 2nd and final visit respectively (p=80 mmHg) was gradually decreased from 61(64.2%) patients to 29(30.5%) patients during enrollment and final visit respectively.Conclusion: The single pill combination of amlodipine/valsartan is significantly reduced the blood pressure among the hypertensive patients in real world settings.Cardiovasc. j. 2016; 9(1): 13-18